The optimal disposition policy for remanufacturing systems with variable quality returns. (February 2020) - Farahani, Sajjad; Otieno, Wilkistar; Omwando, Thomas
Highlights: Disposition decision is the key strategic consideration in remanufacturing systems. Intricate trade-off between the quality value and the recoverable inventory capacity. The system configurations depend on returns quality, inventory size and demand. Abstract: A key strategic consideration in any remanufacturing system is to ensure accurate disposition decisions for returns to maximize the process efficiency and overall profit margin. The purpose of this paper is to develop a disposition decision-making model for a remanufacturing process in which the inventory capacity of recoverable returns is limited, there's a constant demand to be met, and the remanufactured product must meet a minimum quality grade threshold. The paper presupposes that the quality of returns is uncertain and remanufacturing cost is dependent on the quality grades. In this model, remanufacturing takes place when there is demand for remanufactured products. Accepted returns that meet the minimum quality threshold undergo the remanufacturing processes, and any unacceptable returns are salvaged. A continuous time Markov chain (CTMC) is presented and the Matrix-Geometric method is applied to evaluate several key performance metrics for this system and depict the optimal disposition policy. Our numerical study shows an intricate trade-off between the acceptable quality value and the recoverable inventory capacity. Particularly, there is periodic system starvation whenever there is a mismatch between these two system values. As a result, changes to the demand rate for remanufactured products has a great impact on the need to re-evaluate the existing system configuration.